The Influence of Lack of Parental Attention on Children's Learning Motivation at the Barokah Islamic Boarding School, Gonilan Village, Kartasura District - Mufidatul Azizah; Mahasri Shobahiya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to explore the impact of parental neglect on children's learning motivation at TPQ Barokah, Gonilan Village, Kartasura District. The research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and document studies. The research subjects included children studying at the TPQ Barokah, their parents, and teachers. The findings indicate that a lack of parental attention, such as minimal involvement in learning activities, absence of guidance during tasks, and poor communication between parents and children, contributes to a decline in children's learning motivation. Children who receive less attention tend to exhibit low levels of participation in learning, lack discipline, and have lower self-confidence in the learning process. Conversely, consistent parental attention significantly enhances children's enthusiasm and interest in learning, both at home and in the TPQ Barokah environment. This study highlights the crucial role of parental involvement as a key factor in supporting children's educational success. The findings recommend increasing parental awareness of their role in supporting children's education and fostering closer collaboration between educational institutions and families to create a more supportive learning environment.